Elaboración de un restaurante que implementa la colorimetría en sus panes, ubicado al norte de Quito - Vásconez Guerra, Miguel Eduardo (2016)
This project is based on the innovation of new alternatives, offering the customer a product that is main bread, with a new approach based on the color and also providing nutritional values with a healthy diet, taking care thereby feeding the customer. The market study was determined to be an affordable project within the proposed area is commercial, banking and administrative city of Quito and is planned for opening in different parts of the country.